Nutritious food education and the practice of providing complementary foods are appropriate in efforts to prevent stunting - Ayu Rahmadani, Risna; Prasetyowati, Prasetyowati; Aris Tyarini, Indrawati; Rahagia, Rasi; Martha Paseno , Matilda (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2025)
Stunting is a chronic nutritional problem still a public health challenge in Indonesia. One of the factors contributing to the high prevalence of stunting is the lack of knowledge of parents, especially mothers, about balanced nutritional intake and proper practices of feeding Complementary Breast Milk (MP-ASI). This community service activity aims to improve the knowledge and skills of mothers under five related to the importance of nutritious food and the practice of giving MP-ASI in accordance with the guidelines of WHO and the Ministry of Health of the Republic of Indonesia. The methods used are education through interactive counseling, demonstrations of making local food-based MP-ASI, and question and answer sessions. The target of the activity was 40 mothers with children aged 6-24 months in the Posyandu in the assisted area. The evaluation results showed an increase in participants' knowledge by 65% after participating in educational activities. In addition, 80% of participants stated that they were motivated to implement MP-ASI feeding practices that are in accordance with the principles of balanced nutrition. This activity also encourages the use of affordable and nutritious local food resources. With the increase in mothers' knowledge and skills in compiling and delivering MP-ASI, it is hoped that the risk of stunting in early childhood can be minimized. This service activity proves that education-based interventions and direct practices can effectively support programs to accelerate stunting reduction at the community level. The recommendation for the future is to expand the scope of similar activities with cross-sectoral collaboration, especially among health workers and posyandu cadres.